Atrakcyjność projektu metodologii praktycznej i epistemologii cnoty dla badań historyczno-gospodarczych - Bębnowski, Damian (Annales. Etyka w Życiu Gospodarczym, 2015)
Ewa Domańska, Professor at the Adam Mickiewicz University in Poznań (Poland) and Stanford University (USA), historian of historiography and methodologist of history, formulated interesting comments about the state of humanities and social sciences. The development of interdisciplinary research causes the interpenetration of different disciplines. Although this kind of research is promising, inspiring as well as influencing the development of science, careless research may cause some threats in the longer term. According to Domańska, the lack of qualifications and reliability in this area (especially in the area of theory and methodology) undermines the authonomy of the main disciplines and decline in the professionalism of research. This led the author to create the project, which aims to defend the independence of the threatened disciplines as well as their ‘re-professionalisation’. It can be achieved by strongly emphasizing the role of theory in science; a strong embeddement of a discipline in the theory. Domańska’s concept can be a recipe, which is a dichotomic project. Firstly, it supposes a ‘practical methodology’, which is a constructing of the theory thanks to empirical research material. Secondly, it supposes a ‘virtue epistemology’, which is the ethical aspect of the researcher’s attitude and his work. The aim of the paper is to discuss Domańska’s project and underline the originality of her concept in the context of economic and social sciences. The economic history is a specific discipline which develops at the crossroad of history and economics. It lets me put forward the thesis that Domańska’s suggestions are relevant to the research of economic history. I will show what cognitive chances are the result of the ontology of economic history. I will question what the possible threats are for the main disciplines (history and economics) as a result of the lack of professionalism in the interdisciplinary research of the economic past, and ask if Domańska’s project is attractive for the economic history research thanks to the strong setting in the ‘practical methodology’ in the theory. I also ask what the role of new theoretical approaches in that area is, and whether it is possible to formulate innovatory conceptions in the economic history. Finally, I question the role of ‘virtue epistemology’ or the ethical aspect of an economic historian’s work.